2020
DOI: 10.1093/ejcts/ezaa189
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term outcomes with the use of extracorporeal membrane oxygenation for cardiopulmonary failure secondary to massive pulmonary embolism

Abstract: OBJECTIVES There has been increasing interest in using extracorporeal membrane oxygenation (ECMO) to rescue patients with pulmonary embolism (PE) in the advanced stages of respiratory or haemodynamic decompensation. We examined mid-term outcomes and risk factors for in-hospital mortality. METHODS We conducted a retrospective study of 36 patients who required ECMO placement (32 veno-arterial ECMO, 4 veno-venous) following acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Corsi et al interviewed 7 patients at a mean follow-up of 19 months post-hospital discharge using the SF-36 and found QoL impaired compared to a sex- and age-matched control [ 13 ]. Similar findings are reported by Sertic, with patients strongly limited concerning physical, but preserved mental health [ 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…Corsi et al interviewed 7 patients at a mean follow-up of 19 months post-hospital discharge using the SF-36 and found QoL impaired compared to a sex- and age-matched control [ 13 ]. Similar findings are reported by Sertic, with patients strongly limited concerning physical, but preserved mental health [ 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…Of those patients that survived to discharge, most were discharged without sequalae from a PE, including resolution of any RV dysfunction. 43 Looking further into the impact of precannulation CPR, Sertic et al demonstrated that those patients that had return of spontaneous circulation prior to cannulation had superior short-and mid-term outcomes as well as a lower rate of cerebrovascular accidents when compared with those who were placed on ECMO while actively undergoing CPR. 43 In another study by George et al, looking at patients who required ECMO for massive PE, 65.5% survived until decannulation and 53.1% survived to discharge.…”
Section: Outcomes Of Patient With Massive Pe On Ecmomentioning
confidence: 99%
“…43 Looking further into the impact of precannulation CPR, Sertic et al demonstrated that those patients that had return of spontaneous circulation prior to cannulation had superior short-and mid-term outcomes as well as a lower rate of cerebrovascular accidents when compared with those who were placed on ECMO while actively undergoing CPR. 43 In another study by George et al, looking at patients who required ECMO for massive PE, 65.5% survived until decannulation and 53.1% survived to discharge. In this study, the most common causes of death were unrecoverable hemodynamic collapse, gastrointestinal bleeding, ischemic colitis, and hemorrhagic stroke.…”
Section: Outcomes Of Patient With Massive Pe On Ecmomentioning
confidence: 99%
See 2 more Smart Citations